The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1155/2020/3896948
|View full text |Cite
|
Sign up to set email alerts
|

Pingkui Enema Alleviates TNBS‐Induced Ulcerative Colitis by Regulation of Inflammatory Factors, Gut Bifidobacterium, and Intestinal Mucosal Barrier in Rats

Abstract: Background. Ulcerative colitis (UC) is a chronic recurrent inflammation of the colon, and clinical outcome of UC is still unsatisfied. Pingkui enema, a traditional Chinese medicine prescription, has been safely applied for the treatment of diarrhea and dysentery in clinic for many years. However, its mechanism is still elusive. The present study is designed to investigate the effect of Pingkui enema on trinitrobenzene sulfonic acid- (TNBS-) induced ulcerative colitis (UC) and possible mechanism in rats. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…We have shown that Bifidobacterium decreased in the UC group, suggesting that TNBS reduced the content and colonization ability of Bifidobacterium. The imbalance of the bacterial community in TNBS-induced UC is consistent with previous reports ( Becker et al, 2015 ; Yun et al, 2020 ). Bifidobacterium can repair the impaired intestinal epithelial barrier function and reduce IFN-γ secretion in the intestinal mucosa ( Pozo-Rubio et al, 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…We have shown that Bifidobacterium decreased in the UC group, suggesting that TNBS reduced the content and colonization ability of Bifidobacterium. The imbalance of the bacterial community in TNBS-induced UC is consistent with previous reports ( Becker et al, 2015 ; Yun et al, 2020 ). Bifidobacterium can repair the impaired intestinal epithelial barrier function and reduce IFN-γ secretion in the intestinal mucosa ( Pozo-Rubio et al, 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, an increase in Lactobacillus was observed in UC mice after FMT treatment. Most of the current results prove that Lactobacillus is also the main genus used for the treatment of UC (Yun et al, 2020). For example, Liu et al reduced intestinal lining inflammation by rectal enemas of Lactobacillus.…”
Section: Discussionmentioning
confidence: 85%
“…and can induce autoimmune and inflammatory diseases. 32,33 The pro-inflammatory and profocal effects of IL-1β can induce autoimmune and inflammatory diseases. 34 As recently reported, GSDMD is present in nigericin-induced NLRP3 inflammasomes, which act at sites of inflammatory activation and participate in the inflammatory response and IL-1β secretion.…”
Section: ■ Discussionmentioning
confidence: 99%